The Effectiveness of Passive Range of Motion (ROM) Exercise on Motor Recovery in Post-Spinal Anesthesia Patients - Mariani Mariani; Novia Heriani; Candra Kusuma Negara; Ricky Prawira (GLOBAL HEALTH SCIENCE GROUP, 2025)
Spinal anesthesia is a commonly used regional anesthetic technique in surgical procedures, but it is often associated with delayed motor recovery postoperatively. Passive Range of Motion (ROM) exercise is a physiotherapy intervention that has the potential to accelerate motor recovery by stimulating the neuromuscular system and enhancing peripheral blood circulation. This study aimed to evaluate the effectiveness of passive ROM exercises on motor recovery in patients after spinal anesthesia. A quasi-experimental design with a posttest-only control group approach was used. This study used consecutive sampling to recruit respondents who met the inclusion criteria. The sample consisted of 30 patients who underwent spinal anesthesia and were evenly divided into an intervention group (n = 15) and a control group (n = 15). The intervention group received passive ROM exercises for 24 hours postoperatively in four scheduled sessions, while the control group received standard postoperative care. The data analysis used was univariate analysis to describe the characteristics of respondents, while bivariate analysis used the Mann-Whitney test to assess differences in Bromage scores. Motor recovery was measured using the Bromage Scale every four hours. A significant difference in Bromage scores was found between the intervention and control groups at the 24th hour (p = 0.019), with the intervention group showing a lower median score (0) compared to the control group (1), indicating faster motor recovery. Passive ROM exercise is effective in accelerating motor recovery in post-spinal anesthesia patients and can be recommended as part of postoperative care protocols.